Digital payments in Africa - how demand, technology, and regulation disrupt digital payment systems. (25th November 2019) - Ferguson, Kenzie K.; Soutter, Leigh; Neubert, Michael
The purpose of this study is to better understand the impact factors behind the adoption of digital payment systems in Africa. The FinTech environment is changing rapidly and requires constant review of the ecosystem of financial technology innovations to keep abreast of the innovations. This study addresses a gap in the literature regarding the payment and money transfer segment of FinTech innovations in Africa using a multiple case study methodology from Kenya, South Africa, and Nigeria. We pulled information from multiple sources, including semi-structured interviews, archival data in the form of industry and regulatory reports, and observational field notes. The results highlight how regulatory innovation (Kenya) better enables the success of new technologies and their concomitant behavioural change than bank-led (South Africa) and pre-emptive (Nigeria) regulatory styles. This study will help FinTech innovators, academics, and policymakers to understand how technology and framework conditions impact payment business models in Africa.